2012
DOI: 10.2166/wst.2012.225
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical residues in the Danube River Basin in Serbia – a two-year survey

Abstract: Pharmaceuticals are emerging contaminants with damaging effects to the environment and human health. Their presence in surface and especially groundwaters is regarded as detrimental, as they can ultimately reach drinking water. The aim of this work was to monitor pharmaceutical contamination of the Danube River and its tributaries in Serbia, and to assess the potential of their passing through all natural filtrations and reaching the groundwater. A total of 70 surface and groundwater samples was collected at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Bromazepam levels were considerably higher than levels reported in France (Aminot et al, 2015), but this could partially be explained by the distance between sampling sites and STPs, bromazepam was only detected in sampling points directly downstream of STPs, with only a few exceptions. No lorazepam was detected in this study despite the fact it is one of the most prescribed benzodiazepines in both Germany and the UK and previous studies have shown levels of low ng L -1 levels (Vulliet and Cren-Olivé, 2011) and in the range of 6-25 ng L -1 in France, 1.6-37 ng L -1 (Camilleri et al, 2015) and 34-149 ng L -1 (Mendoza et al, 2014b) in Spain, and at 34 ng L -1 in one sampling point in the Danube (Radovic et al, 2012). No degradation of lorazepam was observed during three-month storage at -18 °C and LOQ of methods used are comparable to these previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…Bromazepam levels were considerably higher than levels reported in France (Aminot et al, 2015), but this could partially be explained by the distance between sampling sites and STPs, bromazepam was only detected in sampling points directly downstream of STPs, with only a few exceptions. No lorazepam was detected in this study despite the fact it is one of the most prescribed benzodiazepines in both Germany and the UK and previous studies have shown levels of low ng L -1 levels (Vulliet and Cren-Olivé, 2011) and in the range of 6-25 ng L -1 in France, 1.6-37 ng L -1 (Camilleri et al, 2015) and 34-149 ng L -1 (Mendoza et al, 2014b) in Spain, and at 34 ng L -1 in one sampling point in the Danube (Radovic et al, 2012). No degradation of lorazepam was observed during three-month storage at -18 °C and LOQ of methods used are comparable to these previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…Relatively little information on the contamination of the Danube River or its tributaries by organic chemical substances is available in the public domain ( Loos et al, 2010 ). However, since JDS2 in 2007, research findings have been published regarding contamination of the Danube in Serbia with pharmaceuticals ( Radović et al, 2012 ), constituents of personal care or home cleaning products ( Milic et al, 2014 ), caffeine ( Grujić Letić et al, 2015 ) and pesticides ( Antić et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…in the Danube River in Serbia were monitored in order to determine the potential health risks and possibility of these contaminants passing through all natural filtrations and depositing in the groundwater (Radovic et al, 2012). To accomplish this, 70 samples were taken in 2009 and 2010, and tested in order to understand the health risks of Water Environment Research, Volume 85, Number 10-Copyright © 2013 Water Environment Federation 1957 pharmaceuticals.…”
Section: Pharmaceuticals Pharmaceutical Contaminantsmentioning
confidence: 99%